IMPLEMENTASI SISTEM PAKAR DIAGNOSA PENYAKIT PADA IKAN HIAS MENGGUNAKAN METODE FORWARD CHAINING BERBASIS DESKTOP - Ahmad Ferdiansyah; Aryo Nur Utomo (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
The Covid-19 pandemic has made people more creative and created activities that can reduce stress levels to fill their free time while at home. One of the activities carried out is maintaining ornamental fish. However, ornamental fish lovers often have difficulty knowing the diseases in the fish they have. This research aims to make it easier for the public to diagnose diseases suffered by ornamental fish by using the main scope of artificial intelligence, namely expert systems. This expert system was designed using the waterfall method, several stages including system requirements analysis, design, coding and testing. The expert system is designed using the forward chaining method which can draw conclusions in the form of disease from several symptoms. This research uses the Python programming language, the software used is Visual Studio Code and produces an expert system that can diagnose 8 diseases and their symptoms suffered by ornamental fish Keywords: Expert System, Forward Chaining, Ornamental Fish, Python, Visual Studio Code.